How to kill a witch : the patriarchy's guide to silencing women - Venditozzi, Zoë, 1975-; Mitchell, Claire (Sourcebooks, 2025)
"In the summer of 1563, Scotland was in a bad way. The land was poor, the people were poorer; crops failed, and people starved. In times like these, people looked for anyone to blame, and who easier than the Devil himself? Or, better yet, the women the Devil used to perform his evil deeds. It was in these circumstances that the men of Scotland drafted the Witchcraft Act of 1563. The Act had one basic aim: to stop the Devil and his lackeys (mainly women) from wreaking havoc on a country already beset with problems. And it was from there that the witch-hunt craze spread across the world-eventually landing in the USA. With the wit and humor that have been hallmarks of their popular Witches of Scotland podcast, Claire Mitchell and Zoe Venditozzi explain the process of identifying, accusing, trying, and ultimately killing a woman as a witch, revealing the inner workings of a world organized to protect the patriarchy and preserve the status quo. HOW TO KILL A WITCH is a feminist take on a piece of deeply misogynistic history, perfect for readers of You Never Forget Your First and Killing the Witches"-- Provided by publisher.